STAT3 deficiency in B cells exacerbates uveitis by promoting expansion of pathogenic lymphocytes and suppressing regulatory B cells (Bregs) and Tregs - Oladipupo, Favour O. (Sci Rep, 2020)
STAT3 transcription factor induces differentiation of naïve T cells into Th17 cells and loss of STAT3 in T cell prevents development of CNS autoimmune diseases. However, function of STAT3 in the B lymphocyte subset is not well understood. In this study, we have generated mice lacking STAT3 in CD19(+) B cells (CD19-STAT3KO) and investigated intrinsic and extrinsic functions of STAT3 in B cells and its potential role in resistance or pathogenesis of organ-specific autoimmune diseases. We show that STAT3 regulates metabolic mechanisms in B cells with implications for bioenergetic and metabolic pathways that control cellular homeostasis in B cells. Thus, loss of STAT3 in CD19-STAT3KO cells perturbed growth and apoptosis by inducing rapid entry of B cells into the S-phase of the cell cycle, decreasing expression of cyclin-dependent kinase inhibitors and upregulating pro-apoptotic proteins. We further show that the CD19-STAT3KO mice develop severe experimental autoimmune uveitis (EAU), an animal model of human uveitis. Exacerbated uveitis in CD19-STAT3KO mice derived in part from enhanced expression of costimulatory molecules on B cells, marked increase of Th17 responses and increased recruitment of granulocytes into the neuroretina. The enhanced autoimmunity upon deletion of STAT3 in B cells is also recapitulated in experimental autoimmune encephalitis, a mouse model of multiple sclerosis and thus support our conclusion that STAT3 deletion in B cells enhanced inflammation and the effects observed are not model specific. Our data further indicate that STAT3 pathway modulates interactions between B and T cells during EAU resulting in alteration of lymphocyte repertoire by increasing levels of autoreactive pathogenic T cells while suppressing development and/or expansion of immune-suppressive lymphocytes (Bregs and Tregs). Taken together, STAT3 exerts diametrically opposite effects in lymphocytes, with loss of STAT3 in B cells exacerbating uveitis whereas Stat3 deletion in T cells confers protection.